NR2F6 promotes the malignant progression of neuroblastoma as an indicator of poor prognosis - Yimeng Liu; Zhaoxia Zhang; Tao Mi; Liming Jin; Zhaoying Wang; Mujie Li; Jinkui Wang; Xin Wu; Junyi Luo; Jiayan Liu; Chunnian Ren; Dawei He (PLoS ONE, 2025)
Background NR2F6 is an orphan nuclear receptor with dual tumorigenic activity in the immune system and tumor cells, playing an essential role in tumor differentiation and immunity. This study aimed to investigate the expression level of NR2F6 in various tumors and its effect on neuroblastoma (NB). Methods We evaluated the role of NR2F6 in the genesis and development of 34 different tumors through multiple databases. In addition, we investigated the effects of NR2F6 expression levels on NB risk factors and prognosis using pathology sections and clinical data from primary retroperitoneal NB in children. The effects on cell proliferation, invasion, and migration were explored by knocking down NR2F6 expression in SK-N-BE(2) and SK-N-SH cells. Results The findings showed that NR2F6 was significantly correlated with the prognosis of NB and was an important indicator suggesting disease regression. In addition, NR2F6 knockdown slowed down NB cells’ proliferation, invasion, and migration ability in vitro. Conclusion Our results suggest that NR2F6 plays a crucial role in tumor-promoting effects and can be used as a potential prognostic marker for NB.